2009
DOI: 10.1111/j.1471-4159.2009.06357.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine reduces vesicular dopamine content in dexamethasone‐differentiated PC12 cells only following l‐DOPA exposure

Abstract: Amphetamine (AMPH) increases brain dopamine (DA) levels via reversal of the membrane DA transporter. Additional mechanisms have been suggested, including inhibition of vesicular monoamine transporters and vesicular leakage of DA and Ca2+. According to the widely‐accepted weak base theory, AMPH disrupts the proton gradient required for filling vesicles with DA. As a result, DA and Ca2+ will leak from vesicles, giving rise to exocytosis of less‐filled vesicles. As several contradictions have been described, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Consistent with region-specific actions of AMPH on vesicular dopamine stores, we have recently shown that AMPH may up-regulate vesicular dopamine release in the ventral striatum by mobilizing the reserve pool but by activating dopamine synthesis and inhibiting dopamine degradation in the dorsal striatum [65]. Different distributions of small, clear and large, dense-core vesicles in the two striatal sub-regions [66] may also contribute to the differential response to AMPH. Clearly, more work needs to be done to resolve the differential depleting effects of AMPH on dopamine vesicles in the dorsal and ventral striatum.…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with region-specific actions of AMPH on vesicular dopamine stores, we have recently shown that AMPH may up-regulate vesicular dopamine release in the ventral striatum by mobilizing the reserve pool but by activating dopamine synthesis and inhibiting dopamine degradation in the dorsal striatum [65]. Different distributions of small, clear and large, dense-core vesicles in the two striatal sub-regions [66] may also contribute to the differential response to AMPH. Clearly, more work needs to be done to resolve the differential depleting effects of AMPH on dopamine vesicles in the dorsal and ventral striatum.…”
Section: Discussionsupporting
confidence: 60%
“…An action at synaptic vesicles has been proposed to occur by displacement of dopamine from synaptic vesicles via a “weak base mechanism” that collapses the acidic vesicular pH gradient and/or interactions with the vesicular transporter34. However, the hypothesis that amphetamine affects synaptic vesicle transmitter stores under pharmacologically relevant conditions remains controversial and it has been reported that amphetamine does not, in fact, redistribute dopamine from vesicles35. The mechanism of amphetamine has also been investigated by performing measurements at PC12 cells and at the dopaminergic nerve of Planorbis corneus 32.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesized DA is stored in synaptic vesicles for release. Significant leakage of transmitter molecules out from vesicles has been observed [ 16 , 17 , 18 , 19 , 20 ], and we tentatively assume that leakage also occurs in vivo. Upon arrival of an action, potential vesicles are emptied, and DA is released into the synaptic cleft.…”
Section: Figurementioning
confidence: 59%
“…There is evidence that catecholamine transmitters stored in vesicles leak into the cytoplasm [ 16 , 17 , 18 , 19 , 20 ]. An analysis of the kinetic data by Fried [ 16 ] and Schonn et al [ 17 ] ( Appendix B ) show that the vesicular leakage of DA can be described as a first-order process with respect to (Equation (12)).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation